Optimization and Experiment of Linear Motor Platform Servo Control Algorithm - Wang, Shu; Wu, Xiaoyan (Manufacturing Technology Journal, 2023)
In view of the linear motor servo control system has the advantages of high speed, high response characteristics, in order to adapt to the motion precision, response speed and stability requirements of high precision movement occasions, combined with fuzzy control theory, the design of linear motor platform servo control system fuzzy adaptive PID control algorithm. At the same time, based on LabVIEW software, combined with USB-6009 data acquisition card produced by NI company, the experimental platform for linear motor motion control is designed. Through simulation experiments, the position tracking accuracy, disturbance resistance and response speed of linear motor can be greatly improved. The experimental results achieve the expected control effect, which provides a control method for related research. Therefore, the fuzzy adaptive PID composite control can combine the advantages of both and improve the control effect.
Keywords: Linear motor; Servo system; Control algorithm; Adaptive; Theory of ambiguity